The assessment of slope stability and rock excavatability in a limestone quarry - Kadir Karaman; Bayram Ercikdi; Ayhan Kesimal (Earth Sciences Research Journal)
The aim of this study is to evaluate the stability and excavatability of newly stripped rock slopes (slope 1 (SN–1), slope 2 (SN–2), and slope 3 (SN–3)) in a limestone quarry. These are new production sites with comparable geological formations along the southern part of the quarry where three planar failures were previously observed. For this reason, detailed fieldwork was performed to determine the properties (spacing, roughness, etc.) of the discontinuities of the rock slopes in the study area. The shear strength parameters of the discontinuities and the point load strength index (Is(5o)) and the uniaxial compressive strength (UCS) of rock samples obtained from the study area were tested in the laboratory. The stability of the slopes was assessed using kinematic analysis and an orientation–dependent and orientation–independent slope stability probability classification (SSPC) system. The results of the SSPC system analyses were compared with those of the slope mass rating (SMR). The kinematic analysis shows that planar, wedge and toppling failures are unlikely in the slopes of the study area. The orientation–dependent SSPC analysis revealed that SN–2 would experience sliding failure if its dip angle is greater than 66°. The slopes were shown to have a stability probability of ≥80%, provided that a pneumatic hammer or blasting methods are used for the excavation. However, the maximum slope height (Hmax) in blasting operations is required to be lower for durable slope faces. Furthermore, the SMR analysis has indicated that SN–1 and SN–2 will most likely lose their stability when blasting is used as an excavation method. The rock slopes could be excavated by pneumatic hammer because the category of excavatability of the rock was determined to be ‘easy ripping.’ Based on the kinematic, SSPC and SMR analyses, the angles for a safe slope are proposed to be 70°, 66° and 75° for SN–1, SN–2 and SN–3, respectively, with a slope height of 8 m.